Effects of Intercropping on Plant Nutrient Uptake in Various Vegetables Species - Unlu, H.; Ozdamar Unlu, H.; Dasgan, H.Y.; Solmaz, I.; Sari, N.; Kartal, E.; Uzen, N. (Asian Journal of Chemistry, 2010)
The objective of this study was to determine the effect of intercropping system on some vegetables nutrient uptake in Adana ecological conditions. The experimental research was conducted under field conditions and at the plant physiology laboratory of the Department of Horticulture, Faculty of Agriculture of Cukurova University during 2003-2005. In the first year of this work, cauliflower and broccoli, in the second year cauliflower, cabbage and lettuce were used as main crop. Lettuce, pea, leek, garlic and onion were used as intercrops in the first year; green bean, pea, radish, leek, garlic and onion were used as intercrops in the second year. In general, it can be said that the vegetables cropped solely uptaked more mineral contents while for those grown by intercropping and competitions were determined in intercropped systems.